Infectious bursal disease: evaluation of maternal immunity and protection by vaccination of one-day old chicks against challenge with a very virulent virus isolate - HLS Moraes; CTP Salle; VP Nascimento; FO Salle; ACGP Rocha; GF Souza; TQ Furian; JO Artencio (Brazilian Journal of Poultry Science, 2005)
Broiler chicks belonging to two poultry companies, A and B, with different breeders' vaccination programs were challenged with a very virulent strains of infectious bursal disease virus (vvIBDV), genotyped as G11. Birds were separated in four groups, two vaccinated at the first day of life and two unvaccinated. They were then challenged at the 1st, 4th, 7th, 10th, 13th, 16th, 19th and 22nd days. At every day of challenge, before and after the procedure, the following data were collected from each group: Bursa of Fabricius (BF) relative weight, BF diameter, BF for histologie examination, serum for measuring antibodies against IBDV through the ELISA and clinical evaluation of IBD. The results obtained have shown a non-significant drop in antibody level between the vaccinated and the unvaccinated groups. When analyzing the different results, it could be established that an ELISA titre of 3,4 log10 was the cutoff point between healthy and sick birds. Regression equations were built to determinate the best moment for vaccination and also the ELISA log titre birds what could present in a given age. Based on that, chicks from Company A should receive a vaccine against IBD from the 6th to 7th day of age, while the ones from Company B should get it between the 11th and the 12th day of age. Finally, the overall results suggest that the birds should not be vaccinated at one day old, and also that the breeders' different vaccination schemes resulted in progenies with different levels of maternal protection, and as a consequence the same vaccination plan should not be applied indiscriminately to broilers from different poultry companies.